Investigation of Optimized Density of States (DOS) Analysis, UV-Visible Spectroscopy, NMR Spectroscopy, and Molecular Electrostatic Potential (MEP) Mapping of Ru-486 and Its Derivatives - Kebiroğlu, Mehmet Hanifi; Ak, Fermin (My University, 2025)
When used in combination with misoprostol, RU-486 (Mifepristone) offers a highly effective and non-invasive option for managing early pregnancy loss (EPL), providing a suitable alternative to surgical interventions. In this study, quantum computational chemistry methods were employed to calculate the structural and spectroscopic properties of the Ru-486 molecule and its derivatives (CH2CH3, CH3, F). The molecule was optimized using Density Functional Theory (DFT/B3LYP) with the B3LYP/6-31G basis set. Density of States (DOS) Analysis, UV- Visible Spectroscopy, NMR Spectroscopy, and Molecular Electrostatic Potential (MEP) Mapping were investigated. The compound exhibited HOMO-LUMO band gaps ranging from 3.19 to 4.02 eV, with principal vibrational peaks at 3076 cm?¹ observed in the FT-IR spectrum and maximum UV absorption detected at 408 nm. Additionally, a discussion of the basic theory behind the characterization methods is included.
Keywords: MEP; NMR; DOS; UV-Vis; Ru-486